P68 Clinical experience with Nimbus after failed stentretriever thrombectomy – another chance for recanalization?. (29th August 2022) - Dorn, F; Bode, F; Lehnen, N
Abstract : Introduction: Despite overall high recanalization success, mechanical thrombectomy is unsuccessful in 12 to 41% of patients. 1 The Nimbus device was designed to effectively remove specifically fibrin-rich clots, which often cannot be removed by conventional stent retrieval and/or aspiration procedures. High effectiveness was demonstrated in the model. 2 Aim: To evaluate the clinical experience and recanalization success with Nimbus as a second line device after failed stentretriever thrombectomy of large vessel occlusions. Methods: Consecutive Nimbus cases from one high volume stroke center were retrospectively analyzed. Results: Nimbus was used in 20 patients with acute large vessel occlusion (12 M1-, 8 M2-segment) after unsuccessful recanalization attempts with convential stentretrievers (average 2.36 passages, maximum 6). In 10/20 patients (50%), Nimbus resulted in a TICI 2b-3 outcome wth an average of 2.3 passages (maximum 5). Five of the 10 successful cases were achieved with one single Nimbus pass (50%). Conclusions: The use of Nimbus resulted in a good recanalization outcome in 50% of patients and is therefore a rescue option in otherwise unsuccessful recanalization procedures. References: Goyal M et al . Endovascular Thrombectomy after Large-vessel Ischaemic Stroke: A Meta-analysis of Individual Patient Data from Five Randomised Trials. Lancet 2016 Apr 23;387 (10029):1723–31. DOI: 10.1016/S0140-6736(16)00163-X. EPUB 2016 Feb 18. PMID: 26898852.Sidiqui Fennell VS, Setlur Nagesh SV, Meess KM, et al . What to Do about Fibrin Rich 'Tough Clots'? Comparing the Solitaire Stent Retriever with a Novel Geometric Clot Extractor in an in Vitro Stroke Model. J Neurointerv Surg 2018 Sep;10 (9):907–910. DOI: 10.1136/Neurintsurg-2017-013507. EPUB 2018 Jan 19. PMID: 29352061. Do you have any conflict of interest to declare? : Yes Conflict of Interest Statement: FD serves as a proctor and consultant for Balt, Cerenous, Cerus Endovascular, Stryker and Acandis.